Probabilistic bond strength prediction between the corroded reinforcing bars and concrete considering the concrete strength and non-uniform corrosion. (28th November 2022) - Wu, Jieqiong; Zhang, Xiaowang; Guo, Li; Jin, Liu; Du, Xiuli
Highlights: Bond strength between non-uniformly corroded bars and concrete is discussed. Cross-section area along the corroded bar length follows the lognormal distribution. Uncertainties of the cross-section area of rebars and concrete strength are considered. Probabilistic bond strength is predicted by using the Monte-Carlo method. Abstract: The bond strength considering concrete strength and non-uniformly corrosion was tested by twelve beam-type specimens, and the corrosion was characterized by the 3D scanner. According to the K-S test, the cross-sectional area of the corroded bar follows the lognormal distribution at the 5% significance level, where its mean and standard deviation linearly correlate with the mass loss rate. The probabilistic bond strength is predicted by the Monte-Carlo method, incorporating the uncertainties of the cross-sectional area of rebars and the concrete strength. It is indicated that the failure probability can be decreased by decreasing mass loss rate and increasing concrete strength.